Aggregation and internalisation of electricity externalities in South Africa. (15th March 2015) - Thopil, George Alex; Pouris, Anastassios
Abstract: Energy-environmental impacts associated with non-renewable electricity generation have attained critical importance in South Africa. These impacts are quantified in order to obtain a monetary cost relative to local electricity prices. The methodology used to perform the analysis is the Impact Pathway Approach. Numerous energy-environmental external impacts have been evaluated in this study. The primary externality contributors were found to be GHG (green-house gas) emissions and public health effects from coal combustion. Other minor but important contributors to externalities are also identified and mentioned within the paper. Aggregated central externality costs were found to range from 5.86 to 35.36 SA c/kWh (1.31–7.95 US c/kWh), with central externalities estimates at 13.43 SA c/kWh (3.02 US c/kWh). These central estimates were found to be 68.5% of average electricity prices during the year 2008. Conversion of externality costs from South African currency to US currency has been made with purchasing power parity exchange rates for the year 2008. This study provides sufficient methodological parity for countries with similar electricity generation backgrounds in Southern Africa and Africa as well as other developing countries, considering South Africa generates roughly 45% of the electricity on the African continent. Highlights: Externality analysis of non-renewable electricity generation in South Africa. ExternE methodology used first time in South Africa and Africa. Social and environmental cost analysis of non-renewable electricity generation. International benchmarking of South African electricity prices. Internalisation and pricing analysis/proposals of electricity policy.